Power struggles: An exploration of the contribution of renewable energy to sustainable development, decent work and the “just transition” through a case study of wind farm development outside Loeriesfontein, Northern Cape Province (2011-2020) - Malope, Boitumelo James (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.